Evaluating the effectiveness of energy efficient and eco-leveling ICT infrastructures for environmental sustainability - Hussain Masud, Mosharrof; Abdul Malik, Noreha; Shukran, Md. Khaled (2012)
—This article portrays a critical issue of environmental pollution caused by the extensive use of high technology for ICT development process all over the world which creates a challenge for global sustainability. ICT infrastructures produce numerous environmental pollutions during of its production and disposal. Therefore, it is very important to discard the electronic waste in proper ways to ensure the sustainable environment by adoption of green technology. In this regard, this paper evaluates the energy consumption scenario in the field of ICT and its effect on environment. Following this issue depiction of green technology and its advancement along with a model has been proposed for green adoption which may ensure the sustainable environment. This paper also draws an attention of designing energy efficient computing system and ecoleveling ICT products which are ‘feasible and economical’, and minimizing the risk of human health as well as decreasing pollution towards the environmental sustainability. And finally current advancement as well as future challenges has been addressed in this paper.